2011
DOI: 10.1152/ajprenal.00304.2010
|View full text |Cite
|
Sign up to set email alerts
|

ASARM peptides: PHEX-dependent and -independent regulation of serum phosphate

Abstract: Increased acidic serine aspartate-rich MEPE-associated motif (ASARM) peptides cause mineralization defects in X-linked hypophosphatemic rickets mice (HYP) and "directly" inhibit renal phosphate uptake in vitro. However, ASARM peptides also bind to phosphate-regulating gene with homologies to endopeptidases on the X chromosome (PHEX) and are a physiological substrate for this bone-expressed, phosphateregulating enzyme. We therefore tested the hypothesis that circulating ASARM peptides also "indirectly" contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(162 citation statements)
references
References 59 publications
(167 reference statements)
5
155
0
2
Order By: Relevance
“…14,67 In addition, increased acidic serine aspartate-rich MEPEassociated motif (ASARM) peptides cause the mineralization defects in HYP mice. 20,74 Thus, inactivating mutations of either Phex or Dmp1 produce similar intrinsic bone mineralization defects as well as increased FGF23 expression by osteocytes. Comparative analysis of the Phex-mutant HYP mouse and Dmp1 null mouse showed that PHEX and DMP1 both regulate bone mineralization by inhibiting FGF23 production.…”
Section: Discussionmentioning
confidence: 99%
“…14,67 In addition, increased acidic serine aspartate-rich MEPEassociated motif (ASARM) peptides cause the mineralization defects in HYP mice. 20,74 Thus, inactivating mutations of either Phex or Dmp1 produce similar intrinsic bone mineralization defects as well as increased FGF23 expression by osteocytes. Comparative analysis of the Phex-mutant HYP mouse and Dmp1 null mouse showed that PHEX and DMP1 both regulate bone mineralization by inhibiting FGF23 production.…”
Section: Discussionmentioning
confidence: 99%
“…The ASARM peptide, a motif in MEPE and DMP1, is a substrate for PHEX in vitro (1). Additional data suggest that accumulation of ASARM as a consequence of inactivation of Phex can impair mineralization (129) and phosphate homeostasis (29). We have shown that ASARM binds to and inhibits PHEX activity against a synthetic substrate in vitro (115), but it is unlikely that ASARM from MEPE is responsible for stimulating FGF23 in Hyp, since ablation of MEPE fails to alter FGF23 expression in Hyp mice (30, 112).…”
Section: Fgf23 Regulationmentioning
confidence: 99%
“…Male wild-type (WT) or mutant X-linked hypophosphatemic rickets mice (Hyp) were used for the study (n ϭ 6) and maintained on a 1% phosphorus and 2.41 U/g vitamin-D 3 diet (Harlan Teklad Rodent Diet 8604, Indianapolis, IN) (18). As reported previously, Hyp mice had major increases in circulating ASARM peptide compared with WT (6,13,17,18).…”
Section: Animals and Dietsmentioning
confidence: 99%